The Effect of Intervention Package Massage Therapy, Music Therapy, and Aromatherapy (P, M, A Therapy) on Breast Milk Adequacy - Stia Pusporini, Lenny; Musfirowat, Fifi; Nurjamilah, Siti; Puspasari Ayu, Ike (KnE Social Sciences, 2023)
Effective breastfeeding is the main effort to create optimal life and baby viability. Breastfeeding that is not optimal can be affected by maternal and baby factors. Optimization of breastfeeding can be done with complementary therapy, such as massage therapy, music therapy, and aromatherapy. This study aims to find out the effect of intervention package massage therapy, music therapy and aroma therapy (P, M, A Therapy), on breast milk adequacy at Baros Public Health Center. This study used a quantitative research design, Quasy Eksperimental research design with pre and posttest without control with a research sample of 20 respondents that was taken by using a total sampling technique. The study’s result average respondent before an intervention was 35,85, standard deviation 2,560, CI 95% 34,63-37,05. The average respondent after an intervention was 40,35, standard deviation 2,834, CI 95% 39,02-41,68. The results of the statistical test obtained p-value of 0,00 and 0, it was concluded that there was an effect of the PMA therapy on breast milk adequacy. We hope that in future this intervention package can be developed for achieving optimal breastfeeding. Keywords: intervention package, massage therapy, music therapy, aromatherapy (P, M, A therapy), breast milk